Visualizing Afrofuturism through Mise-en-Scène: Constructing African Cultural Identity in Black Panther (2018) - Haekhal Ahmad Gumilang; Andang Saehu; Yoga Sudarisman (Journal of English Language and Education, 2026)
Film serves as a powerful medium for expressing cultural identity and ideological narratives through visual representation. Black Panther (2018) has been widely discussed in relation to Afrofuturism, yet many studies emphasize its cultural impact rather than examining how Afrofuturism is constructed through cinematic visual design. This research aims to analyze how mise-en-scène visualizes Afrofuturism and African cultural identity in the film, focusing on setting, costume, and lighting. The study applies a qualitative visual analysis based on Gillian Rose’s visual methodology, supported by the mise-en-scène theory of Bordwell and Thompson and the Afrofuturism framework proposed by Dery and Womack. The analysis of selected scenes shows that the film strategically combines traditional African aesthetics with futuristic technological imagery to construct Wakanda as an Afrofuturistic cinematic space. The research concludes that mise-en-scène functions as a visual language that communicates cultural empowerment, technological imagination, and the redefinition of African identity.